Simultaneous Factors Affecting Toddler Nutritional Status - Yoany M. Vianney Bita Aty; Elisabeth Herwanti; Rohana Mochsen (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2021)
The province with the highest percentage of malnutrition among children aged 0-59 months in 2018 was East Nusa Tenggara. The number of toddlers experiencing malnutrition in the Feapoi Health Center area, Rote Ndao district, fluctuated from 2013 to 2017 ranging from 3-12 cases. In 2020, data on 31 toddlers were malnourished and 7 were malnourished based on body weight divided by age (W/W). Efforts made by the Rote Ndao government to reduce stunting and malnutrition are education, routinely providing Supplementary Feeding (PMT), but the incidence of malnutrition and stunting is still high. The study was conducted to analyze the simultaneous factors that affect the nutritional status of toddlers in the Feapoi Health Center area, Rote Ndao Regency. This type of research is quantitative, the design is case control. The research sample consisted of 38 well-nourished toddlers and 38 undernourished toddlers. The research instrument was a questionnaire and a Healthy Towards Card. Univariate data analysis was descriptive, bivariate analysis used Chi Square with a significant level of 5% (α = 0.05), multivariate with multiple logistic regression. The results showed that the factors that simultaneously affected the nutritional status of toddlers in the Feapoi health center, Rote Ndao district were a history of low birth weight (p = 0.014, OR 0.109, 95% CI: 0.18-0.638), and toddlers with exclusive breastfeeding (p = 0.000, OR 0.063, 95% CI 0.18-0.215). It is recommended for further research on health promotion efforts for pregnant women to reduce the risk of low birth weight (LBW) and increase exclusive breastfeeding.